High Concentrations of Uric Acid Inhibit Endothelial Cell Migration via miR‐663 Which Regulates Phosphatase and Tensin Homolog by Targeting Transforming Growth Factor‐β1. (May 2015) - Hong, Quan; Yu, Shandong; Geng, Xiaodong; Duan, Liping; Zheng, Wei; Fan, Men; Chen, Xiangmei; Wu, Di
Abstract: Background: Whether microRNAs participate in endothelial dysfunction HUA remains unknown. A previous study indicated that miR‐663 was the most significantly differentially expressed endothelial microRNA under HUA conditions. Some studies have demonstrated that the miR‐663 target gene and TGF‐ β 1, promoted endothelial cell migration by inhibiting PTEN deleted on chromosome 10. Therefore, we hypothesized that HUA inhibits endothelial migration via miR‐663, which regulates PTEN by targeting TGF‐ β 1. Methods: PCR analysis was performed to determine miR‐663 expression levels. A luciferase assay was performed to validate whether miR‐663 targets TGF‐ β 1 directly. Western blot analysis was performed to determine TGF‐ β 1 and PTEN expression levels. An miR‐663 inhibitor and TGF‐ β 1‐ and PTEN‐specific siRNAs were transfected into EA.hy926 cells to inhibit miR‐663, TGF‐ β 1, and PTEN expression, respectively. A wound healing assay was performed to determine the migratory ability of EA.hy926 cells. Results: miR‐663 had higher expression levels in HUA‐stimulated endothelial cells and in the sera of hyperuricemic patients and animals. TGF‐ β 1 was targeted directly by miR‐663. Endothelial miR‐663 was up‐regulated under HUA conditions, and HUA inhibited endothelial cell migration via miR‐663, which targeted TGF‐ β 1. Thus, TGF‐ β 1 regulated cell migration in a PTEN‐dependent manner. Conclusion: HUA inhibits endothelial cell migration via miR‐663, which regulates PTEN by targeting TGF‐ β 1.